Post-Colonial Feminism in India: Model of Emergent Female Grassroots Leaders in Ahmedabad, Gujarat - Meena Razvi (Adult Education Research Conference, 2007)
A qualitative study explored perceptions of poverty alleviation among female grassroots leaders within informal work sectors of Ahmedabad. Post-colonial feminist approaches enabled women to develop and practice their own model of justice. Conclusions include implications for research, scholarship, and practice in the larger context of women’s development.